The p–gen nature of M₀(V ) (I) - Scott, S.D. (Algebra and Discrete Mathematics, 2013)
Let V be a finite group (not elementary two) and p ≥ 5 a prime. The question as to when the nearring M₀(V) of all zero-fixing self-maps on V is generated by a unit of order p is difficult. In this paper we show M₀(V) is so generated if and only if V does not belong to one of three finite disjoint families D#(1, p) (=D(1, p) ∪ {{0}}), D(2, p) and D(3, p) of groups, where D(n, p) are those groups G (not elementary two) with |G| ≤ np and δ(G) > (n − 1)p (see [1] or §.1 for the definition of δ(G)).